Uji Kevalidan Dan Keterbacaan Instrumen Tes HOTS Berbasis 3TMC Tema Menjaga Tekanan Darah Untuk Siswa Kelas VIII - Nadiyah Azzahra; Sjaifuddin Sjaifuddin; Kurniasih Septi (UNIB Press, 2023)
The concept of science is abstract so that it requires contextual learning in order to grow students' cognitive. One of the efforts is by implementing learning and assessment that measures the level of ability as a whole, such as applying a diagnostic assessment at the HOTS level. The purpose of this research was to determine the validity and legibility of the HOTS test instrument based on 3TMC on the theme of maintaining blood pressure. This research refers to the Thiagarajan model consisting of 3 stages, namely: define, design, and develop. The subjects of this study were 2 material expert lecturers, 2 evaluation expert lecturers, 3 practitioners, and 30 grade VIII junior high school students. Data was collected using interview sheets, validation sheets, and readability questionnaires.The results of the validity of the instrument obtained an average percentage of 92.1% in the very valid category so that the 3TMC-based HOTS test instrument can be used as an evaluation tool. Furthermore, the product was revised and reduced so as to obtain a readability proportion of 86.5% in the very good category which proves that the product loading material is understandable, presented in an attractive manner, written in easy-to-understand language, and the presentation of tables and figures is appropriate.